Excitability regulation in the dorsomedial prefrontal cortex during sustained instructed fear responses: a TMS-EEG study - Gonzalez-Escamilla, Gabriel (Sci Rep, 2018)
Threat detection is essential for protecting individuals from adverse situations, in which a network of amygdala, limbic regions and dorsomedial prefrontal cortex (dmPFC) regions are involved in fear processing. Excitability regulation in the dmPFC might be crucial for fear processing, while abnormal patterns could lead to mental illness. Notwithstanding, non-invasive paradigms to measure excitability regulation during fear processing in humans are missing. To address this challenge we adapted an approach for excitability characterization, combining electroencephalography (EEG) and transcranial magnetic stimulation (TMS) over the dmPFC during an instructed fear paradigm, to dynamically dissect its role in fear processing. Event-related (ERP) and TMS-evoked potentials (TEP) were analyzed to trace dmPFC excitability. We further linked the excitability regulation patterns to individual MRI-derived gray matter structural integrity of the fear network. Increased cortical excitability was demonstrated to threat (T) processing in comparison to no-threat (NT), reflected by increased amplitude of evoked potentials. Furthermore, TMS at dmPFC enhanced the evoked responses during T processing, while the structural integrity of the dmPFC and amygdala predicted the excitability regulation patterns to fear processing. The dmPFC takes a special role during fear processing by dynamically regulating excitability. The applied paradigm can be used to non-invasively track response abnormalities to threat stimuli in healthy subjects or patients with mental disorders.